2009
DOI: 10.1002/jctb.2274
|View full text |Cite
|
Sign up to set email alerts
|

Development of mixing time correlation for a double jet mixer

Abstract: BACKGROUND: Jet mixing is one of the simplest methods to achieve mixing. There have been a number of experimental studies concerned with jet mixing; some of these studies report empirical correlations. The existing correlations are not useful where there are significant deviations from the idealized conditions. Most correlations reported in the literature deal with liquid flow with single or multiple jets, whereas the effect of radial angle on mixing time was not studied. This present study investigates the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…6 The jet mixer has several advantages over the mechanical mixer because it has a low sealing problem, 7 low energy consumption, 1 cheaper installation, 8 and a lower mixing time. 9 For the mixing of the liquid−liquid phase, the jet system has a higher liquid mixing and mass-transfer operation. 10 Over the years, the jet device has been used for the treatment of wastewater and acid extraction, but the studies were found to be limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The jet mixer has several advantages over the mechanical mixer because it has a low sealing problem, 7 low energy consumption, 1 cheaper installation, 8 and a lower mixing time. 9 For the mixing of the liquid−liquid phase, the jet system has a higher liquid mixing and mass-transfer operation. 10 Over the years, the jet device has been used for the treatment of wastewater and acid extraction, but the studies were found to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…The plunging jet can be used for the mixing of different liquids, which can be achieved by using other mixer processes such as the jet mixer and the mechanical or static mixer . The jet mixer has several advantages over the mechanical mixer because it has a low sealing problem, low energy consumption, cheaper installation, and a lower mixing time . For the mixing of the liquid–liquid phase, the jet system has a higher liquid mixing and mass-transfer operation .…”
Section: Introductionmentioning
confidence: 99%
“…7 Mixing time as a function of impeller eccentricity has been studied for a turbulent regime of Newtonian liquid flow. The results of experimental studies of mixing time in a stirred tank with dual eccentrically located impellers were presented by Woziwodzki et al 8 An experimental analysis of the effect of operational parameters on mixing time in a double jet mixer was presented by Manjula et al 9 Computational and experimental investigations of mixing time in a fully baffled stirred vessel with two six-blade Rushton turbines were reported by Zadghaffari et al 10 Both numerical and experimental studies of mixing time for coaxial mixing in a co-rotating or counter-rotating operation, when Newtonian and non-Newtonian fluids are employed in the laminar-transitional regime, were given by Rivera et al 11 Mixing time measurements in dual-impeller gas−liquid reactors were presented by Bouaifi and Roustan. 12 A gas hold-up and the mixing time in a forced circulation loop reactor with a novel type of gas sparger were reported by Fadavi and Chisti.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, estimation of residence time distribution (RTD) of each parcel of water is important, because they are used to calculate expected hydraulic and water quality efficiencies for specific designs. Although a number of field (Palau et al 2007;Grayman 2000;Stamou 2002), laboratorial (Rossman andGrayman 1999;Tian and Roberts 2008;Manjula et al 2010), and computational (Patwardhan 2002;Stamou 2002;Marek et al 2007;Raja et al 2007Raja et al , 2008Stamou 2008;Zhang et al 2012Zhang et al , 2013Zhang et al , 2014Xavier et al 2014) experiments have been carried out to investigate the influence of design and operation factors upon hydraulic and water quality indexes, they are inconclusive on at least four issues.…”
mentioning
confidence: 99%